G86 Psychological aspects of child health: Workshops for paediatric trainees. (27th April 2016) - Jacob, H; Cryer, J; Emanuel, L; Laurent, S; Roth, S
Abstract : Aims: Paediatricians often see children and young people with emotional difficulties manifesting as physical illness, sometimes called medically unexplained symptoms. Mental health training for general paediatricians is often lacking which can result in over-medicalisation of the problem. Recent political and media attention has been focused on the need to improve mental health provision for child and young people. Given the demands on Child and Adolescent Mental Health Services, attempts at improving the skills of paediatricians in assessing and treating children with medically unexplained symptoms could help ease pressure and improve care. Methods: We evaluated the impact on paediatric trainees' confidence of a series of workshops about medically unexplained symptoms. Five workshops were facilitated by a Consultant Child and Adolescent Psychotherapist and took the form of case discussions. The primary outcome measure was trainees' self-reported confidence in assessing and managing child and young people with medically unexplained symptoms. Results: Thirteen trainees participated in the workshops. Self-reported confidence in assessing children and young people with medically unexplained symptoms was higher after the workshops (difference in confidence +0.88, 95% CI 0.21–1.56, p = 0.023). Trainees' confidence in formulating and discussing a management plan was also increased (difference in confidence +1.00, 95% CI 0.57–1.43, p = 0.004). Participants identified that the workshops had increased their awareness of the psychological aspects of illness with one describing having a "better idea of the myriad of ways that psychological distress may manifest in children and young people". Trainees also described an increasing willingness to reflect on their own response to children, young people and families with medically unexplained symptoms. Conclusion: Reflective workshops for paediatric trainees improve their confidence in assessing and managing children and young people with medically unexplained symptoms. Given that this is a common presentation to general paediatricians and that they often feel unconfident managing mental health problems, we believe such workshops could be usefully incorporated into postgraduate paediatric training. Further studies will evaluate the impact on clinical outcomes and the feasibility of multi-professional training.